Unlocking therapeutic precision: "Camptotheca acuminata, a traditional chinese herb tailored for phytonano-cancer theranostics" - Debojyoti Adak; Priyanka Ray; Saini Setua (Elsevier, 2024)
Introduction: In recent years, there has been a growing interest in leveraging traditional medicinal plants for modern therapeutic approaches, particularly in cancer treatment. The review explores the potential of Camptotheca acuminata, a traditional Chinese plant, in cancer treatment through innovative phytonano-based drug delivery systems. Camptotheca acuminata contains camptothecin, a potent anticancer compound, but its therapeutic use is hindered by poor solubility, bioavailability, and systemic toxicity. The study highlights how phytonano-technology can enhance therapeutic accuracy and reduce side effects by using nanoparticles to encapsulate and selectively deliver drugs directly to cancer cells. This approach could significantly improve oncology therapy by addressing the limitations of traditional chemotherapy. Methods: Using PubMed and Scopus, prospective research on the medicinal and anticancer activities of several Chinese mushroom species during the past 20 years were searched. The query included ''Camptotheca acuminata,'' ''cancer,'' ''nanoparticles,'' ''traditional Chinese medicine,'' and ''theranostics.'' Only entire English-language articles were used. Results: Phytonano-Cancer Theranostics with camptothecin effectively targets cancer cells, showing substantial uptake in vitro and prolonged circulation and accumulation at tumor sites in vivo. These results demonstrate its potential for precise and effective cancer therapy. Discussion: The integration of camptothecin with Phytonano-Cancer Theranostics offers promising targeted drug delivery and theranostic capabilities in cancer therapy. However, challenges remain, including optimizing nanoparticle design for stability, scalability, and biocompatibility, and overcoming biological barriers for efficient tumor targeting. Addressing these challenges requires interdisciplinary research to maximize the potential of innovative strategies and improve cancer patient outcomes.